2022
DOI: 10.1007/s00011-022-01568-0
|View full text |Cite
|
Sign up to set email alerts
|

A new mouse unilateral model of diffuse alveolar damage of the lung

Abstract: Objective and design The existing biological models of diffuse alveolar damage (DAD) in mice have many shortcomings. To offset these shortcomings, we have proposed a simple, nonsurgical, and reproducible method of unilateral total damage of the left lung in ICR mice. This model is based on the intrabronchial administration of a mixture of bacterial lipopolysaccharide (LPS) from the cell wall of S. enterica and α-galactosylceramide (inducing substances) to the left lung. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
(41 reference statements)
1
5
0
Order By: Relevance
“…In our previous study [15], we successfully demonstrated that E. coli-induced acute lung injury using ICR mouse showed significant increases in lung injury, including alveolar congestion, hemorrhage, neutrophil infiltration, and alveolar wall thickness, as well as inflammatory cytokine levels, which are similar to those observed in clinical ALI/ARDS [18]. The ICR mouse strain is commonly used in in vivo disease models, including acute lung injury, as reported in other previous studies [19,20]. Furthermore, it is known that C57BL/6 mice and ICR mice have similar physiological features and metabolic phenotypes [21].…”
Section: Discussionsupporting
confidence: 58%
“…In our previous study [15], we successfully demonstrated that E. coli-induced acute lung injury using ICR mouse showed significant increases in lung injury, including alveolar congestion, hemorrhage, neutrophil infiltration, and alveolar wall thickness, as well as inflammatory cytokine levels, which are similar to those observed in clinical ALI/ARDS [18]. The ICR mouse strain is commonly used in in vivo disease models, including acute lung injury, as reported in other previous studies [19,20]. Furthermore, it is known that C57BL/6 mice and ICR mice have similar physiological features and metabolic phenotypes [21].…”
Section: Discussionsupporting
confidence: 58%
“…Five animals from each group were sacrificed at day 7 and 45 and histological studies were performed, as described previously [55,92]. Briefly, the lungs were filled with 10% solution of neutral formalin, embedded in paraffin and 4–5 μm width sections were stained with hematoxylin and eosin.…”
Section: Methodsmentioning
confidence: 99%
“…These features limit statistical analysis and yield binary “yes or no” result of the experimental therapy. Here we assessed therapeutic effect of dexamethasone, tocilizumab and TAK- 779 on the course of the ARDS in non-lethal, highly reproducible ICR DAD murine model mimicking SARS-CoV-2 infection [55] using histological evaluation, cytokine profiling and computed tomography analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Infection of mice with the SARS-CoV-2 virus. Thirty-six days after the first immunization, all C57BL/6-TgTn(CAG-humanACE2-IRES-Luciferase-WPRE-polyA) mice were transferred to a specialized ABSL-3 level laboratory (Sergiev Posad), where they were infected with the Wuhan SARS-CoV-2 strain by intranasal administration of the SARS-CoV-2 virus at a dose of 3 log PFU in a volume of 20 μL of saline [38]. In mice that died during the observation period, the cardiopulmonary complex was extirpated and, after two weeks of inactivation in 10% formalin solution, was sent for histological examination.…”
Section: Assessment Of the Protective Efficacy Of Formulation L 1 In ...mentioning
confidence: 99%